2015
DOI: 10.1186/s12941-015-0101-5
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular characterization of clinical isolates of Acinetobacter baumannii isolated from Delhi, India

Abstract: BackgroundAcinetobacter has gained importance as a multi-drug resistant and hence a difficult to treat pathogen. This study was done to characterize our isolates with respect to drug resistance and presence of beta-lactamases which is a major mechanism of resistance and to type using RAPD and MLST so that comparison of our clones can be made with the existing international clones.Methods100 isolates recovered from clinical samples from two hospitals in Delhi were tested for their susceptibility against major g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
36
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 24 publications
12
36
2
Order By: Relevance
“…The resistance of A. baumannii isolates to cephalosporins in the present study was in accordance with another study conducted by Safari et al, 2013 [5]. Ciprofloxacin resistance rate (92.9%) was similar to studies conducted in Egypt and India which showed resistance rate of 85% and 99%, respectively [22, 23]. …”
Section: Discussionsupporting
confidence: 90%
“…The resistance of A. baumannii isolates to cephalosporins in the present study was in accordance with another study conducted by Safari et al, 2013 [5]. Ciprofloxacin resistance rate (92.9%) was similar to studies conducted in Egypt and India which showed resistance rate of 85% and 99%, respectively [22, 23]. …”
Section: Discussionsupporting
confidence: 90%
“…Our results indicated that all A. baumannii isolates were MDR and carbapenem resistant. The high prevalence of MDR A. baumannii strains is in accordance with the findings reported by Farsiani et al (97%) and Rynga et al (85%) in Iran and India, respectively [20], [21]. The global spread of MDR clones in healthcare settings has raised a great deal of concern, because carbapenem agents are commonly the first choice in the treatment of A. baumannii infections [22], [23].…”
Section: Discussionsupporting
confidence: 84%
“…Carbapenem resistance in A.baumannii has been reported in various studies, ranging from 40-98.7% (5, [21][22][23][24]. We found 86.9% carbapenem resistance in A. baumannii which is similar to 85% resistance reported by Rynga D et al (2015) from Delhi (25). But previous studies conducted in our institute by Pandya et al, (2012) and Kalpesh et al (2016) have reported a comparatively higher resistance to carbapenems i.e.…”
Section: Discussionsupporting
confidence: 84%